Roundtable "Collective Bargaining and Group of Companies" - Sánchez Reyes, Christian (2016)
In this roundtable, our speakers analyze, evaluate and criticize the new legal scenario which is the collective labor law, specifically related to collective bargaining, in an area influenced by the development of capitalism, which is beginning to cause different forms business organizations that break the paradigm of the definition of company we know, and thus leads us to redesign legal parameters to meet the challenges of the now called “business groups” and “network companies” for a proper defense of the collective rights of workers and defend the interests of employers.